Study of Demand for Business Capital Credit at Government Banks in Riau Province - Denada, Putri (Journal of Business Inflation Management and Accounting, 2024)
This research aims to analyze the influence of GDP, interest rates, CPI and the number of deposits on demand for venture capital credit at state banks in Riau simultaneously and partially. The data used is secondary data sourced from Bank Indonesia North Sumatra variables, namely GDP, Interest Rates, CPI and Total Capital Savings and Loans of North Sumatra Province, on a quarterly basis from 2003 to 2011. Data analysis was carried out using OLS (Ordinary Least Square) with multiple linear regression models estimated with the help of the Eviews 5.1 program. The results of the research can be concluded that simultaneously the variable co-GDP constant change, consumer price index, interest rates, and the amount of savings have a significant effect on credit demand in the capital city of Riau Province. Furthermore, it is partially concluded that the GDP variable and the number of deposits have a positive effect on capital credit demand, while the CPI and KPR interest rate variables have a negative effect on credit demand in the capital city of Riau Province. The research results also show that the most dominant variable influencing credit demand in the capital province of Riau is the number of deposits.